Kelayakan Kualitas Perairan Sekitar Mangrove Center Tuban Untuk Aplikasi Alat Pengumpul Kerang Hijau (Perna viridis L.) - Syarifah Hikmah Julinda Sari; Ledhyane Ika Harlyan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2015)
The coastal waters around the Mangrove Center Tuban, East Java is a potential habitat for the green mussel (Perna viridis L.). Therefore, the water quality of this area need to be assessment. The study was aimed to determine the feasibility of water quality in coastal water f Mangrove Center Tuban for application collecting gear of green mussels. The sampling was conducted by set up three stations randomly in studied area. Parameters was measured including temperature, pH, salinity, DO, depth, turbidity, BOD and TSS. The results showed that the coastal waters around the Mangrove Center Tuban, owned temperature that ranged from 29.10 to 30.67 0C, the pH ranged from 8.23 to 8.37, salinity ranged from 26.87 to 30.30 ‰, DO fall in the range of 6,63- 6.87 mg / L, the water depth at the time of measurement ranges from 40-85 cm. TSS ranged from 206.2 mg / L to 353.7 mg / L, BOD value between 4.05 to 12.2 mg / L, while the turbidity ranged from 134 to 400 NTU. Parameters that below the standard namely temperature, pH, DO, salinity and BOD, while TSS and turbidity were exceed the threshold quality standards set by the government.